China's economic presence in Mozambique - Garcia, Francisco Proença (2021)
Our study aims to analyse the Chinese economic presence in Mozambique during the second decade of the 21st century. This objective emerged from the observation of the visible presence in Mozambique of several Chinese com- panies that intervene in different sectors. The choice of this period of analysis is mostly related with the lack of systematized studies about this topic, taking also into consideration that, during this period, Mozambique faced an economic and financial crisis that resulted from a high debt and that led to the interven- tion of the international community. In order to achieve this goal, a central question arises: what are the characteristics of the Chinese economic presence in Mozambique during the second decade of the 21st century? The first part, the framework, briefly describes the Chinese presence in the African continent; in the second part, we will address the relationship between Mozambique and China and will describe spectrally the economic and financial situation in Mozambique; in the third we attempt to estimate the volume of trade between both countries; in the fourth, we analyse China-Mozambique cooperation and China's Official Development Assistance to Mozambique, and; in the fifth, we analyse China's current foreign direct investment in the country.